INTEGRATING LOCAL WISDOM AND CHARACTER VALUES IN DIGITAL MATERIALS FOR RECEPTIVE ORAL LANGUAGE SKILLS - Natalia, Christine Helena; Siregar, Tiarnita Maria Sarjani Br.; Pulungan, Anni Holila; Khairina, Yuni; Batubara, Khairunnisa Br. (Universitas Islam Sumatera Utara, 2025)
This study aimed to develop digital learning materials that integrate local wisdom and character education for the Receptive Oral Language Skills course in the English Education Study Program at Universitas Negeri Medan. Using a Research and Development (R&D) model, the study followed several stages: preliminary study, needs analysis, material design, expert validation, revision, and final product development. Data were collected through questionnaires, interviews, and expert evaluation forms, and analyzed both qualitatively and quantitatively to assess the materials’ quality and feasibility. The developed digital materials were designed to enhance students’ receptive oral skills while embedding character values and local cultural elements from North Sumatra. Expert validation, conducted by specialists in English education, instructional media, and local culture, evaluated linguistic quality, learning process, content integration, and digital design. The results showed an overall score of 91.75%, categorized as “very good.” The final product is a set of digital learning materials that combine cultural relevance, character education, and interactive features to support meaningful learning in Receptive Oral Language Skills. The findings imply that integrating local wisdom and character values into digital learning resources can not only enhance language comprehension but also foster students’ cultural awareness, moral development, and appreciation of local identity. This approach offers a model for culturally responsive and value-oriented language instruction in higher education.